The Role of Servant Leadership in Improving Employee Satisfaction and Performance - Sudiarti, Nani; Hedi Saepudin, Tubagus (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
This study aims to analyse the role of servant leadership in improving employee satisfaction and performance. Servant leadership is a leadership style that emphasises service to subordinates, with the main objective of facilitating employee growth and development. The research method used is a literature study by collecting and analysing various articles and scientific journals related to servant leadership, job satisfaction, and employee performance. The results showed that servant leadership has a positive and significant influence on job satisfaction and employee performance. Servant leaders who prioritise empathy, personal development, empowerment, and ethical behaviour can increase employees' sense of job satisfaction. In addition, servant leadership can also improve employee performance through increased motivation, organisational commitment, and organisational citizenship behaviour.